The biomechanics of pelvic tilt - M. C. Siff (AOSIS, 1991)
Emphasis on the use of pelvic tilt fails to take account of several other types of pelvic rotation involved with three dimensional pelvic stability and mobility. It is necessary to have a thorough understanding of the biomechanics of all types of pelvic rotation in order to safely and efficiently use the spine during all physical activities.